Association of interleukin-8 polymorphism (+ 781 C/T) with the risk of oral Lichen Planus disease - Haniyeh Ghasemi; Hamid Reza Mozaffari; Maryam Kohsari; Masoud Hatami; Kheirollah Yari; Mohammad Hesam Marabi (BMC, 2023)
Abstract Background Oral Lichen Planus (OLP) is a chronic inflammatory mucosal disease. The pathogenesis of OLP is unknown. The Single Nucleotide Polymorphism (SNP) that occurs in the regulatory position + 781 could affect the expression of interleukin-8. This polymorphism is probably associated with increased serum levels of IL-8. The current study aimed to investigate the genotype and allele frequencies of IL-8( + 781 C/T) in OLP patients and whether it is associated with the severity of OLP disease in an Iranian population. Methods Three milliliters of saliva were taken from 100 patients with OLP and 100 healthy individuals who were matched in age and gender. After DNA extraction from saliva samples of patients and healthy individuals, the genotype of IL-8 at position + 781 is detected using the PCR-RFLP method. The results were analyzed using SPSS software. Results Frequency of C/C, T/C, and T/T genotypes at position IL-8 + 781 gene in the patient group were 47%, 41%, and 12%, respectively, and in the control group, were 37%, 42%, and 21%. The difference between the two groups regarding allele frequency distribution was statistically significant (χ2 = 3.86, p = 0.049, 95% CI = 0.44-1, OR = 0.66). Our results indicated the significantly higher frequency of the TT genotype in the erosive OLP compared to the nonerosive group (p = 0.03, OR = 0.89, 95% CI = 0.49-1.6). Conclusion This study depicted the difference in the frequency of SNP IL-8 + 781 C/T allele in the patient and control groups had a significant association with the risk of OLP. In addition, our data revealed that IL-8 + 781 C/T polymorphisms might be associated with the severity of OLP in the Iranian population.